Youth and masculinity from the margins. Sociocultural experiences of young people in detention - Juan Pablo Zebadua Carbonell (Universidad Autónoma de Ciudad Juárez, 2021)
The purpose of this article is to give an account of youth masculinity experienced in what we have called from the sidelines, in the case of young men who are deprived of their liberty in internment Specialized Center for Adolescents (CIEA) Villa Crisol, in Berriozábal municipality, Chiapas. The prison inmates and sociocultural strategies that these young people to live and socialize pose that, in turn, provide insight into the plurality of experiences and experiences of men according to their class, age, sexual orientation, gender, ethnicity analyzed and skin color. Thus, (re) construct their masculinity, many times invisible, marginalized or oppressed within a broad framework of power relations.